Characterization of metagenome-assembled genomes of two endo-archaea of Candida tropicalis - Jagadeeshwari, Uppada; Sasikala, Chintalapati; Rai, Anusha; Indu, B.; Ipsita, Sahu; Ramana, Chintalapati Venkata (Frontiers in Microbiomes, 2023)
Host-microbe interactions are pivotal in host biology, ecology, and evolution. Recent developments in sequencing technologies have provided newer insights into the same through the hologenome concept. We report here the results of a study on metagenome-assembled genomes (MAGs) associated with Candida tropicalis (studied through shotgun metagenome sequencing), adding to the knowledge about endomicrobiomes of yeast. De novo assembly and binning recovered two partial archaeal genomes, taxonomically belonging to the phylum Asgardarchaeota. The phylogenomic analysis based on the core genes revealed that both the binned genomes cladded separately with the less studied and uncultivated ‘Candidatus’ superphylum, designated as Asgard archaea (the nearest known relative of eukaryotes). Between the two binned genomes, the average nucleotide index (ANI) was 71.2 %. The average nucleotide identities (ANI) of the two binned genomes with ‘Candidatus Heimdallarchaeota’ were 60.4-61.2 %. The metabolic pathways of both the binned genomes predicted genes belonging to sulfur reduction, Kreb’s pathway, glycolysis, and C1 carbon metabolism. Further, both the binned genomes were predicted to support autotrophic as well as the heterotrophic mode of growth, which might probably help the host in its nutritional requirements also. Further, the genomes showed few eukaryotic signature proteins (ESPs) and SNARE proteins indicating that members of Asgardarchaeota are the closest relatives of eukaryotes. The gaps present in the metabolic potential of the MAGs obtained and the absence of a few essential pathways shows that they are probably in a symbiotic relationship with the host. The present study, reports for the first-time endosymbiosis of Asgard archaea with yeast. It also provides insights into the metabolic potential, ecology, evolutionary history, and endosymbiotic nature of the important but poorly studied Asgard archaea.